Kegiatan Sosialisasi dan Edukasi Produk Hukum bagi Pelaku UMKM dan Ekonomi Kreatif di Kelurahan Temberan Kota Pangkalpinang - Yen Yen; Abdul Rasyid Saliman; Feri Frandica; Rian Fauzi; Raffi Akbar; Frendiva Frendiva; Wika Putri; Devita Tritami; Normantri Normantri; Lea Betty; Hardalena Hardalena; M.Abbyzard Dava (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
Community service with the theme of Socialization and Education of Legal Products for MSME and Creative Economy Actors in Temberan Village, Pangkalpinang City, is based on field conditions, where many MSME actors in the region do not have legal legality for the businesses they run and lack basic knowledge regarding product packaging and brand creation that have high marketability. As a result, their businesses are not developing to strengthen the creative economy and enhance the capacity of actors. The model used in this program is a direct dialogue method with the MSME actors. The discussion results showed that of the 26 participants, only 1 MSME actor had received guidance and had an NIB (Business Identification Number), but lacked a halal certificate and patent rights for their product brands. The other 25 participants were briefed for the first time regarding the importance of legal legitimacy for their business. Therefore, it can be concluded that these 25 MSME actors do not have legal legitimacy for their businesses. The team provided assistance to help register their businesses by collaborating with relevant agencies. Regarding product branding, it was found that all participants had not optimized their product branding, as most MSME actors in Temberan Village packaged their products simply without attractive branding, packaging, colors, or packaging materials. Many even used plastic wrapping without a brand. The team intervened intensively by providing further assistance to MSME actors in Temberan Village, utilizing information and communication technology to help determine product brands for those without one and to select packaging materials that follow current trends, shapes, colors, and materials to make the product more attractive and increase branding and consumer interest.